catena-Poly[[cadmium-bis(μ-triethylenetetramine-κ(4) N,N′:N′′,N′′′)-cadmium-(μ-triethylenetetramine-κ(4) N,N′:N′′,N′′′)] hexafluoridogermanate] - Wang, Guo-Ming (International Union of Crystallography, 2011)
The title fluoridogermanate, {[Cd(2)(C(6)H(18)N(4))(3)][GeF(6)]}(n), was synthesized hydrothermally. The crystal structure comprises undulated cationic [Cd(2)(TETA)(3)](4+) chains (TETA is triethylenetetramine) propagating parallel to [101]. The central Cd(II) atom is six-coordinated in a CdN(6) set by three TETA ligands. The isolated [GeF(6)](2−) units, serving as counter-anions, occupy the inter-chain spaces and simultaneously link adjacent chains into a three-dimensional network through extensive N—H⋯F hydrogen-bonding interactions. One of the ethylene bridges of one TETA ligand is disordered around a twofold rotation axis.